2020
DOI: 10.1021/acsami.0c16116
|View full text |Cite
|
Sign up to set email alerts
|

Novel One-Dimensional Covalent Organic Framework as a H+ Fluorescent Sensor in Acidic Aqueous Solution

Abstract: Covalent organic frameworks (COFs) represent an emerging class of two- or three-dimensional crystalline porous materials with delicate control over topology, composition, and porosity. Here, we develop a new COF made up of 1,3,6,8-tetrakis­(p-formylphenyl)­pyrene (TFPPy) and 4,4′-diaminobenzophenone (DABP) that exhibits a rare one-dimensional (1D) structure. The resulting frameworks possess good crystallinity, comparatively high Brunauer–Emmett–Teller (BET) surface area (426 m2/g), and good thermal stability (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…8 Several studies report on COF-based chemosensors for the detection of gaseous hydrochloric acid, 25,26 and a series of aqueous Brønsted acids. 26,27 Recently, Yang et al have studied the effect of imine-protonation on the optical properties of three imine-linked COFs. It was found that all COFs showed a bathochromic shift after acid exposure due to the protonation of the imine bond.…”
Section: Acid-vapour Sensingmentioning
confidence: 99%
“…8 Several studies report on COF-based chemosensors for the detection of gaseous hydrochloric acid, 25,26 and a series of aqueous Brønsted acids. 26,27 Recently, Yang et al have studied the effect of imine-protonation on the optical properties of three imine-linked COFs. It was found that all COFs showed a bathochromic shift after acid exposure due to the protonation of the imine bond.…”
Section: Acid-vapour Sensingmentioning
confidence: 99%
“…We herein report the design and syntheses for azasubstituted conjugated polymers possessing environment responsiveness. Based on the azobenzene 32,33,[35][36][37][38][39][40] and Schiff base [41][42][43][44][45][46] structures, we prepared copolymers with fluorene and bithiophene units. We successfully obtained three types of polymer films and evaluated stimuli responsivity.…”
Section: Introductionmentioning
confidence: 99%
“…27e), through the condensation of 1,3,6,8-Tetrakis(p-formylphenyl) pyrene (TFPPy) and 4,4 0 -diaminobenzophenone (DABP). 215 COF-TP displays pH-dependent fluorescence emission in acidic solution in the pH range of 0-6. The PL intensity shows a linear decrease with the decrease of the pH value, and is almost quenched at pH =0, accompanied by an obvious color change from orange (pH = 6) to black (pH = 0) under both sun and UV light (365 nm) (Fig.…”
Section: Other Sensingmentioning
confidence: 99%